The effect of intensive praziquantel administration on vaccine-specific responses among schoolchildren in Ugandan schistosomiasis-endemic islands (POPVAC A): an open-label, randomised controlled trial - Nkurunungi, Gyaviira; Nassuuna, Jacent; Natukunda, Agnes; Walusimbi, Bridgious (The Lancet Global Health, 2024)
Vaccine responses differ between populations and are often impaired in rural and low-income settings. The reasons for this are not fully understood, but observational data suggest that the immunomodulating effects of parasitic helminths might contribute. We hypothesised that Schistosoma mansoni infection suppresses responses to unrelated vaccines, and that suppression could be reversed—at least in part—by intensive praziquantel administration.